Iconography of Interpreters in the Conquest of the Americas - Araguás, Icíar; Jalón, Jesús (TTR : traduction, terminologie, rédaction)

(untitled) (Association canadienne de traductologie, 2004)
AbstractThis paper focuses on the figure of the interpreter as it appears in the visual images illustrating chronicles and other texts from the period of the Conquest of the Americas by the Europeans. The fact that linguistic and cultural mediation was necessary for an understanding between the cultures is commonly absent from the records, as if direct communication had been possible between both sides-yet another fiction of the encounter. Based on the assumption that visual representations are valuable records to understand the perception of the role of interpreter in the past, we analyze six images of different cultural and ethnic authorship, painted between 1550 and 1619. The aim of the paper is to make a contribution to the task of building the history of interpreting, following a line of research which, as proposed in the conclusion, merits further exploration.